Power Relations in The Context of Unconventional Tin Mining in the PICE Dam Area, Lenggang Village - Rahul Ikhsan; Fitri Ramadhani Harahap; Herdiyanti (Social Science Studies, 2023)
The purpose of this study is to describe all forms of unconventional tin mining practices in the Pice dam area of Lenggang Village, to analyze the process of forming power relations in unconventional tin mining practices in the Pice Dam area and to analyze the implications produced by a relationship in unconventional tin mining practices on social conditions. the local community of Lenggang Village. This study used a qualitative research method with a descriptive analysis approach. Sources of research data come from primary and secondary data. Primary data was obtained through observation and interviews with Tin Miners, Village Heads, Mining Bosses, DLH of East Belitung Regency, Mosque Management and Non-Mining Communities. Secondary data obtained through documentation and various supporting documents. The technique for determining informants used a purposive sampling technique. The theory used to analyze the phenomena in this study is the theory of power relations by Michel Foucault. The results of the study consist of: First, mining practices began based on the transition from Conventional Mining (TK) to Unconventional Mining (TI) with the economic benefits of Rajuk Unconventional Mining (TI) being very high, this occurred as a result of a change in the status of PT Timah from a State Enterprise (PN) to become BUMN which is considered as people's mining. Second, power relations consist of bosses, miners, police, village government and mosque administrators who spread the dominant discourse of mining as power-knowledge. Third, discipline occurs in the form of governmentality such as the death of the resistance movement, bias on educational issues and high levels of consumption due to the low human development index.